An Insight into Non‐Covalent Interactions on the Bicyclo[1.1.1]pentane Scaffold. Issue 7 (22nd December 2020) - Grover, Nitika; Flanagan, Keith J.; Trujillo, Cristina; Kingsbury, Christopher J.; Senge, Mathias O.
Abstract: Bicyclo[1.1.1]pentane (BCP) is studied extensively as a bioisosteric component of drugs. Not found in nature, this molecular unit approximates the distance of a para ‐disubstituted benzene which is replaced in medicines as a method of improving treatments. Predicting interactions of these drugs with specific active sites requires knowledge of the non‐covalent interactions engaged by this subunit. Structure determinations and computational analysis (Hirshfeld analysis, 2D fingerprint plots, DFT) of seven BCP derivatives chosen to probe specific and directional interactions. X‐ray analysis revealed the presence of various non‐covalent interactions including I ⋅⋅⋅ I, I ⋅⋅⋅ N, N−H ⋅⋅⋅ O, C−H ⋅⋅⋅ O, and H−C ⋅⋅⋅ H−C contacts. The preference of halogen bonding (I ⋅⋅⋅ I or I ⋅⋅⋅ N) in BCP 1 –4 strictly depends upon the electronic nature and angle between bridgehead substituents. The transannular distance in co‐crystals 2 and 4 was longer as compared to monomers 1 and 3 . Stronger N−H ⋅⋅⋅ O and weaker C−H ⋅⋅⋅ O contacts were observed for BCP 5 while the O ⋅⋅⋅ H interaction was a prominent contact for BCP 6 . The presence of 3D BCP units prevented the π ⋅⋅⋅ π stacking between phenyl rings in 3, 4, and 7 . The BCP skeleton was often rotationally averaged, indicating fewer interactions compared to bridgehead functional groups. Using DFT analysis, geometries were optimized and molecular electrostatic potentials were calculated on the BCP surfaces. These interaction profiles may be useful for designing BCP analogs of drugs. Abstract : The effect of bridgehead substitutions on non‐covalent interactions was investigated for seven BCP derivatives. The X‐ray analyses show 3D‐structures and a combination of non‐covalent interactions including HB, XB, and CH ⋅⋅⋅ HC contacts. QTAIM analysis and MEP graphs show the presence of bond critical points and σ‐holes.